2002
DOI: 10.1111/j.1572-0241.2002.05783.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and health care seeking in the functional GI disorders: a population-based study

Abstract: More than one third of the general population have one or more FGIDs. There seems to be a modest link between psychological morbidity and FGIDs, although other unknown factors seem to be more important in explaining health care seeking for these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
228
7
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(264 citation statements)
references
References 28 publications
20
228
7
9
Order By: Relevance
“…7 Individuals with IBS are more likely to consume health care resources than healthy individuals, 8 with up to 80% of sufferers consulting their primary care physician as a result of symptoms. 9,10 Diagnosing IBS can be challenging due to overlap between the symptoms that sufferers report and those of organic GI conditions such as celiac disease, [11][12][13] small intestinal bacterial overgrowth, 14 bile acid diarrhea, 15,16 exocrine pancreatic insufficiency, 17 or inflammatory bowel disease. 18 Partly as a result of this uncertainty, symptom-based diagnostic criteria were developed for use by physicians consulting with patients with suspected IBS as early as the 1970s, with Manning et al reporting six symptoms that were commoner among individuals found ultimately to have IBS after investigation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Individuals with IBS are more likely to consume health care resources than healthy individuals, 8 with up to 80% of sufferers consulting their primary care physician as a result of symptoms. 9,10 Diagnosing IBS can be challenging due to overlap between the symptoms that sufferers report and those of organic GI conditions such as celiac disease, [11][12][13] small intestinal bacterial overgrowth, 14 bile acid diarrhea, 15,16 exocrine pancreatic insufficiency, 17 or inflammatory bowel disease. 18 Partly as a result of this uncertainty, symptom-based diagnostic criteria were developed for use by physicians consulting with patients with suspected IBS as early as the 1970s, with Manning et al reporting six symptoms that were commoner among individuals found ultimately to have IBS after investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Population based studies on this particular topic are rare and, in general, have methodological problems (24,28) considering the dif ficulty to exclude structural diseases in a large sample, as required for population studies. Another factor is that the diagnostic criteria for dyspepsia is not standard, although most authors use the criteria suggested by the Rome consensus (6,29,48) .…”
Section: Introductionmentioning
confidence: 99%
“…Em relação às características dessa amostra, deve-se assinalar que o presente estudo foi realizado somente na população que procurou atendimento médico e, portanto, não pode se inferir se a mesma associação deva ser encontrada nos pacientes com DF que não utilizaram os serviços de saúde. Contudo, em estudo de base populacional (14) sobre transtornos gastrointestinais funcionais, utilizando o Critério de Roma I, foi encontrada associação entre DF e morbidade psicológica, sendo que neuroticismo, depressão, ansiedade e angústia somática mostraram-se preditores para DF. Por outro lado, estudo mais recente (11) aponta para um percentual signifi cativamente maior de deprimidos entre os pacientes com DF que procuraram atendimento médico, quando comparados àqueles que não o procuraram.…”
Section: Discussionunclassified